Work-Life Balance: The effect on Absenteeism among Employees in a Malaysian Utility Company - Mohd, Idaya Husna; Shah, Maimunah Mohd; Anwar, Nur Aizureen; Mahzumi, Nadia (International Journal of Economics and Financial Issues, 2016)
Employees spend at least one-third of their day at their work place. Since most of the time is spent at the work place, excess in working hours can cause the employees to feel burned out at the end of the week. These high emotional exhaustion and less personal time will cause the employees to adjust their own time in order to achieve preference hours of work. The utility company involves in this study practices 5.5 working days. Feeling overemployed, this will lead the employees to adjust their behaviour into choosing to be absent from work. Thus, this study focus on to examine: (i) whether working 5.5 days in a week currently implemented by the company has stimulated the employees to be absent from work as one of their effort to achieve a balance in their work-life style (ii) the relationship of Work-Life Balance and absenteeism in a utility company in Malaysia. A survey was conducted among the employees to explore their response towards absenteeism and work-life balance. The findings of this study highlighted the understanding of the work-life balance and absenteeism concept from the employees' perspective. Based on the findings of this research, working excessive hours stimulated the employees to be absent on the last working day of the week. The findings of this study also offer new perspectives which the company may need to consider in order to have employees who are more efficient. Keywords: Work-life balance, Absenteeism, Malaysia, Utility Industry, Burned out. JEL Classifications: M10, M50, M54